Traffic Offload Data antara Jaringan 3G dengan Jaringan WiFi - Fazliadi Rahmatillah; Uke Kurniawan Usman (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2015)
The 3G network infrastructure such as BTS (BaseTransceiver Station), femtocell, picocell is still limited andconsequently still in the process of making data access by userswho are in the building and in public places during rush hourtraffic to be blocked due to density data. Then Traffic Offload /Mobile Data Offload (Seamless Connectivity) could be onesolution for addressing the explosion in data traffic, data trafficon the 3G network transferred over or Traffic Offload to WiFiNetwork (3G-WiFi Traffic Offload). The WiFi Network is able toprovide access data at higher speeds, increasing network capacityand Infrastructure WiFi that can be used together.In this research, Traffic Offload between 3G Network withWiFi network used software MATLAB R2013b. The analysis isdone by observing the received signal strength, handover user,drop user, handover delay and throughput.From the results of this research we have know the ReceivedSignal Strength (RSS) that is appropriate to perform offloadingfrom 3G network to WiFi network are RSS 3G network = -84dBm, RSS WiFi network = -69 dBm so that we get 260 handoverusers and 240 dropped users on user velocity = 50 m/s. Andoffloading from WiFi network to 3G network are RSS 3Gnetwork = -91 dBm, RSS WiFi network = -76 dBm so that we get138 handover users and 111 dropped users on user velocity is 50m/s. For 245 handover users we get handover delay = 40,05 milisecond and user throughput = 2 Mbps in 3G network at 0,1 kmfrom 3G Node B and user throughput = 2,9 Mbps at 50 meterfrom WiFi access point (at 1,5 km from 3G Node